A study on the antibacterial effect of selected medicinal plants of Western Ghats against dental caries bacteria - Shafi Thompson T,; Arunima Ashok,; Sukesh K, (International Journal of Phytomedicine, 2011)
This study was conducted to reveal the antibacterial effect of selected medicinal plants from Western Ghats against dental caries bacteria and aware the populace about the importance of using phytomedicines. In this study, the antibacterial effects of nine well known medicinal plants were checked against the dental caries bacteria using well diffusion method. The highest zonation was reported in acetone and methanol extracts. The Chloroform and ethanol extracts revealed sensible activity and water extracts were produced least inhibitory activity. Acetone extract of Eucalyptus gained high inhibitory activity against Bacillus megaterium. While Pseudomonas aeruginosa showed resistance to all the extracts of Syzygium aromaticum.